Фразеологізми української й англійської мов на позначення температурних відчуттів людини: спільне та відмінне - Нікітченко, Олексій; Nikitchenko, Oleksiy (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті здійснено зіставний аналіз фразеологічних одиниць (далі ФО), що позначають температурні відчуття людини, на матеріалі англійської та української мов. Автор використовує концептуальний і структурно- семантичний підходи в дослідженні проблеми. Важливе значення приділено лінгвокультурологічному й етимологічному аналізу, аналізу словникових дефініцій.In the last years the research of the conceptual picture of the world is one of theactual branches of linguistics coming into being as a result of interaction of language as system and comprehension. Such feelings of a man as hunger, thirst, appetite, gluttony, sleepiness, short breath, perception of sound, voice, smell, light are important forms of comprehension The temperature perception of a man also plays an important role among them. The article deals with the contrastive analysis of idioms denoting temperature perception of a man on the basis of English and Ukrainian. Author uses conceptual, structural and semantic approaches to research the problem. Linguistic and cultural analysis, word definition and etymological analyses are also paid an important attention.
Common and Different Features of Ukrainian and English Phraseological Units which Represent Person's Temperature Feelings
Keywords: відчуття; фразеологічна одиниця; зіставний аналіз; англійська мова; українська мова; feelings; idiom; contrastive analysis; English language; Ukrainian language